Analysis of The Ability to Solve Hots Questions On Measurement Material of PGSD Students Based on Bloom’s Taxonomy - Nabilah Mansur; Arina Najwa, Wulida (IJE : Interdisciplinary Journal of Education, 2025)
A total of 66.7% of Primary Teacher Education (PTE) students demonstrated high-level thinking skills in the high category, while 33.3% were in the moderate category, with none in the low category. Analytical (C4) and creative (C6) skills were relatively strong, though evaluate (C5) varied. This study aimed to analyze students’ higher-order thinking skills (HOTS) in the topic of measurement using the revised bloom’s Taxonomy (C4-C6) as a framework. Six PTE students from STKIP Al Hikmah based essay items and semi-structured interviews. The data were analyzed qualitatively using triangulation techniques. The findings indicate thar, despite most students performing at a high level, inconsistencies in performance across cognitive dimensions suggest uneven mastery of HOTS. This highlights the need to strengthen instructional strategies that foster balanced development of analytical, critical, and creative thinking. The results also imply the importance of embedding HOTS-based assessment and instruction across all fundamental mathematics topics in teacher education curricula, to better prepare prospective teacher for real-world classroom challenges.